From structure to clinic: design of a muscarinic M1 receptor agonist with the potential to treat Alzheimer’s disease - Brown, AJH; Bradley, SJ; Marshall, FH; Brown, GA; Bennett, KA; Brown, J; Cansfield, JE; Cross, DM; Dias, JM; Errey, JC; Hurrell, E; Liptrot, J; et al. (Cell Press, 2021)
Current therapies for Alzheimer’s disease seek to correct for defective cholinergic transmission by preventing the breakdown of acetylcholine through inhibition of acetylcholinesterase, these however have limited clinical efficacy. An alternative approach is to directly activate cholinergic receptors responsible for learning and memory. The M1-muscarinic acetylcholine (M1) receptor is the target of choice but has been hampered by adverse effects. Here we aimed to design the drug properties needed for a well-tolerated M1-agonist with the potential to alleviate cognitive loss by taking a stepwise translational approach from atomic structure, cell/tissue-based assays, evaluation in preclinical species, clinical safety testing, and finally establishing activity in memory centers in humans. Through this approach, we rationally designed the optimal properties, including selectivity and partial agonism, into HTL9936—a potential candidate for the treatment of memory loss in Alzheimer’s disease. More broadly, this demonstrates a strategy for targeting difficult GPCR targets from structure to clinic.